2019
DOI: 10.34117/bjdv5n10-128
|View full text |Cite
|
Sign up to set email alerts
|

Produção e caracterização de pão de forma glúten-free, formulado com farinha de arroz preto, inulina e enzima transglutaminase microbiana

Abstract: Produção e caracterização de pão de forma glúten-free, formulado com farinha de arroz preto, inulina e enzima transglutaminase microbiana Production and characterization of the gluten-free form formulated with black rice flour, inulin and microbian transglutaminase enzyme

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…The sweet potato, as its own name says, is rich in sugars (carbohydrates) that give it a sweet flavor, which is why it influenced the sugar content in breads. The values of total sugars and reducing sugars found by Alencar et al (2019) in breads based on rice flour corroborate the values found in this work because rice also contains carbohydrate sugars.…”
Section: Results Of the Physical-chemical Analysis Of The Breadssupporting
confidence: 90%
“…The sweet potato, as its own name says, is rich in sugars (carbohydrates) that give it a sweet flavor, which is why it influenced the sugar content in breads. The values of total sugars and reducing sugars found by Alencar et al (2019) in breads based on rice flour corroborate the values found in this work because rice also contains carbohydrate sugars.…”
Section: Results Of the Physical-chemical Analysis Of The Breadssupporting
confidence: 90%
“…These pigments are concentrated in the grain's karyopsy, giving it the name "black rice". The use of black rice in the food industry as a raw material is of great relevance, due to its high nutritional value and attractive sensory characteristics (Alencar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%